2007
DOI: 10.3390/medicina43020017
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of clinical evaluation and treatment results of high-energy blunt polytrauma patients

Abstract: The aim of this study was to evaluate the mechanism of high-energy blunt trauma, age and gender of patients, severity of regional and multiple injury, ventilation time, length of stay in intensive care unit and in-hospital stay, in-hospital complications, and treatment outcome. Materials and methods. Data on 159 patients with severe multiple injuries, meeting inclusion criteria, were collected prospectively and evaluated retrospectively. Results. The mean age of multiple trauma patients was 43.9±1.4 years; mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…[5][6][7] Many series derived from the South East Asian region had even younger patients comparing to studies done in the developed countries. [8][9][10][11][12][13][14] Blunt trauma was more frequent than penetrating trauma in our series which is compatible with other series. 2,5,11,12,15 The literature suggest that traffic accidents is the leading cause of chest trauma in most series, our study showed the same picture.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[5][6][7] Many series derived from the South East Asian region had even younger patients comparing to studies done in the developed countries. [8][9][10][11][12][13][14] Blunt trauma was more frequent than penetrating trauma in our series which is compatible with other series. 2,5,11,12,15 The literature suggest that traffic accidents is the leading cause of chest trauma in most series, our study showed the same picture.…”
Section: Discussionsupporting
confidence: 86%
“…2,5,11,12,15 The literature suggest that traffic accidents is the leading cause of chest trauma in most series, our study showed the same picture. 2,5,[8][9][10][11][12][13][14][15][16] Violence was the second leading cause in our series. The current study showed only two centre report, and this result cannot be generalized until a broad-based epidemiological study is performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma has the tendency to affect young males in the productive period of life [ 5 ][ 6 ][ 7 ]. Many series derived from the Middle East region had even younger patients [ 8 ][ 9 ][ 10 ][ 11 ] comparing to studies done in the developed countries [ 12 ][ 13 ][ 14 ]. Blunt trauma was more frequent than penetrating trauma in our series which is compatible with other series [ 2 ][ 5 ][ 11 ][ 12 ][ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blunt trauma was more frequent than penetrating trauma in our series which is compatible with other series [ 2 ][ 5 ][ 11 ][ 12 ][ 15 ]. The literature suggest that traffic accidents is the leading cause of chest trauma in most series [ 2 ][ 5 ][ 8 ][ 9 ][ 10 ][ 11 ][ 12 ][ 13 ][ 14 ][ 16 ]. But violence was the leading cause in our series and exceeded traffic accidents.…”
Section: Discussionmentioning
confidence: 99%